Diversity of Pollinator Insects in Anagro Garden, Bengkulu City, Indonesia - Wisti, Lilis; Apriiarti, Mega Sari; Cahaya, Mariana Ade (Universitas Muhammadiyah Surakarta, 2025)
Pollinator insects are considered beneficial organisms due to their essential role in plant pollination, supporting both ecological stability and agricultural productivity. However, land-use change and pesticide application may reduce pollinator diversity, making it necessary to identify existing species and assess their diversity as indicators of ecosystem health. This study aimed to identify the species and assess the diversity of pollinator insects in Anagro Garden, Bengkulu City. Field research was conducted from January to March 2025 using an exploratory survey method combined with direct observation. Sampling was carried out across multiple points within the garden. The results showed that pollinator insects observed in this area belonged to four insect orders. The calculated Shannon-Wiener Diversity Index (H′) was 1.317, indicating a moderate level of species diversity. The Dominance Index (D) was 0.283, showing that no single order overwhelmingly dominated the assemblage. The Evenness Index (E) was 0.950, reflecting a high level of evenness and very uniform distribution of individuals among species. These findings suggest that although species abundances vary, the pollinator community remains balanced. The moderate diversity level indicates that the ecosystem quality in Anagro Garden is still fairly goodHowever, the study underscores the need for ongoing monitoring and habitat management to enhance pollinator diversity and maintain ecological resilience, particularly in semi-urban agroecosystems like those found in Bengkulu City.